2012
DOI: 10.1002/chem.201201437
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Reversible Chemosensory Polymers: Modulation of Sensitivity through the Attachment of Novel Imidazole Pendants

Abstract: Three novel electron donor-acceptor conjugated polymers (P1-P3) bearing various imidazole pendants have been synthesized. Their excellent photophysical and electrochemical properties make them suitable transduction materials for chemosensing applications. Indeed, polymers P1-P3 have been found to show remarkable sensing capabilities towards H(+) and Fe(2+) in semi-aqueous solutions. Upon titration with H(+), polymers P1 and P2 showed hypsochromic shifts of their absorptions and photoluminescence (PL) maxima wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…1 H NMR analysis indicated that 3 contains only the Z -isomer since it is more thermodynamically stable due to the presence of a hydrogen bond between oxygen and 4-hygrogen . The overall yield of 3 starting from 1 was 70%, which may be further increased based on the higher yield (up to 92%) reported for the formation of 2 in the bromination step. , This is much higher than the overall yield of other A monomers that have been used for preparing the BDT-based D–A polymer donors, such as FC-TT (9%), TPD (54%), BDD (32%), FBTA (12%), BT (12%), and Qx (33%) (Figure S1). Moreover, the synthesis of this monomer does not require the use of hazardous reagents, such as n -butyllithium, or harsh reaction conditions, which can further reduce the synthetic complexity …”
Section: Results and Discussionmentioning
confidence: 93%
“…1 H NMR analysis indicated that 3 contains only the Z -isomer since it is more thermodynamically stable due to the presence of a hydrogen bond between oxygen and 4-hygrogen . The overall yield of 3 starting from 1 was 70%, which may be further increased based on the higher yield (up to 92%) reported for the formation of 2 in the bromination step. , This is much higher than the overall yield of other A monomers that have been used for preparing the BDT-based D–A polymer donors, such as FC-TT (9%), TPD (54%), BDD (32%), FBTA (12%), BT (12%), and Qx (33%) (Figure S1). Moreover, the synthesis of this monomer does not require the use of hazardous reagents, such as n -butyllithium, or harsh reaction conditions, which can further reduce the synthetic complexity …”
Section: Results and Discussionmentioning
confidence: 93%
“…Ethyl-4-methyl-2-phenylthiazole-5-carboxylate (emptzH), 31 1,10-phenanthroline-5,6-dione, 32 2,9-dimethyl-1,10-phenanthroline-5,6-dione, 33 ethyl-3,4-diaminobenzoate, 34 ethyldipyrido[3,2-a:2′,3′-c]phenazine-11-carboxylate (edppz), 35 pyridylimidazo[4,5-f ][1,10]phenanthroline ( piphen), 14 were synthesised according to the literature methods or subtle variations thereupon.…”
Section: Synthesismentioning
confidence: 99%
“…Besides NMR also mass spectrometry [52][53][54][55], IR and UV spectroscopy [56,57], chromatography [58,59], atomic force microscopy and scanning tunneling microscopy [60,59] are used to determine polymer microstructure.…”
Section: Polymer Microstructurementioning
confidence: 99%